Elimination and provocation test in cow's milk hypersensitive children - Mulya Safri; Nia Kurniati; Zakiudin Munasir (Indonesian Pediatric Society, 2008)
Background Allergic disease in infancy mostly related to cow'smilk allergy. The prevalence of cow's milk hypersenstivity in chil-dren has increased steadily in the past years; therefore diagnosticaccuracy is important and every symptomatic child with positivespecific lgE should be followed by elimination and provocation.Objective To diagnose cow's milk hypersensitivity on children un-der three years old using elimination and provocation methods.Methods This was a clinical diagnosis study, in which childrenwith allergy symptoms were examined for cow's milk sensitivityusing prick test or lgE Radioallergosorbent test (RAST). Thosewith positive results underwent an elimination for minimal of 2weeks and were challenged aterwards. The study was a qualitativediagnostic test with the gold standard of recurrence of symptomsafter challenge test.Results There were forty subjects included in the challenge pro-cess with mean age of 17 months old. Boys and girls were equallydistributed. There were 6 7% subjects with positive results onchallenge with positive prick test and 64% positive challenge withhistory of positive lgE RAST. Sixty-five percents of subjects withpositive results on challenge had more than 2 weeks eliminationperiod. There was no statistical significance found in childrenwith positive results on challenge, using neither prick test orlgE RAST.Conclusions Cow's milk protein allergy can be diagnosed on chil-dren less than 3 years old by applying elimination and challengeprocedure. lgE sensitivity alone can not determine hypersensitivity